An Interleukin-12-Expressing Oncolytic-Virus Infected Autologous Tumor Cell Vaccine Generates Potent Anti-Tumor Immune Responses - Khan, Sarwat Tahsin (Université d'Ottawa / University of Ottawa, 2018)
An IL-12-expressing oncolytic virus-infected cell vaccine (MG1-IL12-ICV) can prolong survival in murine models of peritoneal carcinomatosis in an NK and CD8+ T-cell dependent manner. However, MG1-IL12-ICV enhances survival but does not provide durable cures in aggressive models of established disease suggesting the presence of immunosuppressive mechanisms. Here we show that MG1-IL12-ICV can generate specific anti-tumor T-cell responses and can delay tumor growth in prophylactic models. We further demonstrate that treatment of mice bearing tumors with MG1-IL12-ICV can recruit CD4+ and CD8+ T-cells and CD11c+ dendritic cells into the tumor microenvironment (TME) and can increase NK cell activity. Regulatory T-cells and myeloid derived suppressor cells do not appear to play a role in immunosuppression following therapy, but checkpoint molecules are upregulated. Overall, this thesis provides strong evidence for the favorable anti-tumor immune TME induced by MG1-IL12-ICV and provides avenues that can be explored to further improve outcomes with MG1-IL12-ICV.
Keywords: Interleukin-12; Whole Cell Vaccines; Infected Cell Vaccine; Oncolytic Virus; Tumor Microenvironment; Tumor Immunology; T-cells; NK cells; Immunosuppression